Investigation on the multi-scale interfacial adhesion characteristics between three kinds of repair materials and calcium-leached concrete - Jianhui Tang; Yin Bai; Wenxun Qian; Dehao Cui; Feng Zhang (Case Studies in Construction Materials, 2025)
Surface protection of calcium-leached concrete is critical for extending the service life of hydraulic infrastructure. This study innovatively combines multi-scale analysis (macro, meso, and micro) to systematically investigate interfacial adhesion characteristics between three repair materials—permeable crystallization (PC), acrylic emulsion cement paste (AECP), and epoxy mortar (EM)—and calcium-leached concrete from a 20-year-old water conveyance tunnel. Macroscopic bond strength was evaluated via pull-off tests, while mesoscale interfacial zone (meso-IZ) properties (porosity, pore distribution, and fractal dimension) were analyzed using X-ray computed tomography. Microscale interfacial zone (micro-IZ) characteristics, including cementation state and thickness, were examined via scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS). Results demonstrated that all repair materials provided protective effect on the leached concrete. From the point of view of pull-off bond strength, EM exhibited the highest bond strength (3.43 MPa), followed by PC (1.14 MPa), while AECP showed the weakest bonding (0.64 MPa). Meso-IZ porosity decreased significantly for PC (0.36 %) and AECP (0.79 %) compared to untreated concrete (1.00 %). EM shows a higher porosity (10.93 %), but more independent pores, indicating a lower risk of leakage. Fractal dimension analysis indicated improved meso-IZ pore uniformity in PC- and AECP-treated leached concrete (0.82–0.86 vs. 0.95 for untreated concrete). SEM-EDS analysis demonstrated that EM formed a denser micro-IZ with a thickness of 46.5 μm, attributable to its superior penetration capability, while AECP showed minimal micro-IZ thickness (26.6 μm) with pore defects. Notably, bond strength inversely correlated with meso-IZ thickness but showed no significant dependency on micro-IZ thickness. This multi-scale analysis highlights the critical role of interfacial pore structure in bonding performance, offering a scientific foundation for optimizing repair strategies in calcium-leached concrete rehabilitation.